Study of the 10B(p,αγ)7Be and 10B(p,p’γ)10B reactions for PIGE purposes - Lagoyannis, A.; Preketes-Sigalas, K.; Axiotis, M.; Foteinou, V.; Harissopulos, S.; Kokkoris, M.; Misaelides, P.; Paneta, V.; Patronis, N. (HNPS Advances in Nuclear Physics, 2019)
N/A